1998
DOI: 10.1183/09031936.98.11051111
|View full text |Cite
|
Sign up to set email alerts
|

Fine particle mass from the Diskus inhaler and Turbuhaler inhaler in children with asthma

Abstract: aaDry powder inhalers (DPI) are increasingly used for aerosol delivery to the airways for the reasons that they are easy-to-use with no requirements of co-ordination, they are convenient and are without propellants or irritants. In addition, an ideal device should provide a high and predictable airway dose and a low pharyngeal dose. In all DPIs the inspiratory airflow of a patient provides the energy source to disperse the agglomerates of micronized powder and to move the respirable particles from the body of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
1
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(55 citation statements)
references
References 9 publications
2
51
1
1
Order By: Relevance
“…The present data demonstrate that 30% of the elderly population were not able to reach the arbitrary cut-off flow of 45 L?min -1 when using a Turbuhaler1, while only 20 and 12.5% of the population had similar problems with the Diskus1 and Aeroliser1, respectively. Turbuhaler1 and Aeroliser1 are less effective at a PIF ,60 L?min -1 , whereas the Diskus1 seems to have an equal effect at a PIF 30-60 L?min -1 [6,[22][23][24][25][26][27][28][29][30]. This could mean that, in contrast to the Diskus1, the number of patients with subtherapeutic flows over the Aeroliser1 or Turbuhaler1 is even underestimated.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…The present data demonstrate that 30% of the elderly population were not able to reach the arbitrary cut-off flow of 45 L?min -1 when using a Turbuhaler1, while only 20 and 12.5% of the population had similar problems with the Diskus1 and Aeroliser1, respectively. Turbuhaler1 and Aeroliser1 are less effective at a PIF ,60 L?min -1 , whereas the Diskus1 seems to have an equal effect at a PIF 30-60 L?min -1 [6,[22][23][24][25][26][27][28][29][30]. This could mean that, in contrast to the Diskus1, the number of patients with subtherapeutic flows over the Aeroliser1 or Turbuhaler1 is even underestimated.…”
Section: Discussionmentioning
confidence: 49%
“…PIFs .60 L?min -1 are generally believed to be the optimal flows for most of the devices, while PIFs ,30 L?min -1 are accepted to be insufficient for generating any effect [6,[22][23][24][25][26][27][28][29][30]. As there is still discussion about the effectiveness of PIFs ranging 30-60 L?min -1 [14,31,32], an arbitrary cut-off at a PIF of 45 L?min -1 was made in order to distinguish therapeutic flows from subtherapeutic levels.…”
Section: Pulmonary Function Measurementsmentioning
confidence: 99%
“…However, it is not the only characteristic parameter. Since the PIFR is mostly achieved after the release of the powder, the slope of the pressure profile (in kPa?s -1 ) has also been described as an important determinant [6,9,10]. The present investigation was undertaken to assess whether the PIFR through a Diskus1 and a Turbuhaler1 inhaler could be used to predict the slope of the inhalation pressure profile.…”
mentioning
confidence: 99%
“…In vitro device evaluations showed that the emitted dose and fine particle mass of the Turbuhaler1 (higher resistivity) increase at higher peak inspiratory flow rates (PIFRs) [5,6], whereas the Diskus1 (lower resistivity) provided a more consistent dose delivery, relatively independent of different airflows [6,7]. However, there was therapeutic equivalence of salbutamol given via these devices [8].…”
mentioning
confidence: 99%
“…The FPF is a maximum at 1 min at 70.07 ± 4.71%. Comparing this to the commercial budesonide turbuhaler DPI, the FPF is reported to be 44% (Ball et al 2002;Bisgaard et al 1998;Thorsson et al 1994;Borgstrom et al 1994). While FPF is almost similar at 10 and 30 min drug loading, at 55.91 ± 6.81% and 55.97 ± 5.97%, respectively.…”
Section: Drug Dispersionmentioning
confidence: 85%